Interferensi dan Campur Kode Di Akun Media Sosial Instagram Angelina Duncan - Artifa Sorraya; Luly Zahrotul Lutfiyah; Tities Hijratur Rahmah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Abstract: This study aims to determine the types of phonological interference that emerged in Instagram Angelina Duncan. The interferences were described textually according to the results obtained from research subjects. The formulation of the problem in this study is hoe is he vowel, consonant, and Javanes language interference in the use of spoken Indonesian in the material criticrizing the personal experience of early chilhood in Instagram Angelina Duncan This type of research is descriptive qualitative. Data was obtained by recording stories that were done by Instagram Angelina Duncan. The data collection method uses the capable engagement method. The result of this study there are three cases tht occur namely 1) the occurance of interference of vowel sound changes such as, changes in pronunciation of vowel /u/ to /o/, /a/ to /e/, /i/ to /e/, and vocal /e/ in the middle of the word. 2) the occuarnce of consonant change in the form of the edition of a letter and a consonant. For example, the edition of the letter /m/ at he begining of the word, /h/ in the middle of the word, at the and of the word, and the removal of the danial /h/ in the middle of the word. 3) the occurance of cluster sound changes in the form of double consonant removal at the and of the word.